Virucidal effect of high power ultrasound combined with a chemical sanitizer containing peroxyacetic acid for water reconditioning in the fresh-cut industry. (June 2015) - Sánchez, G.; Elizaquível, P.; Aznar, R.; Selma, M.V.
Abstract: The use of chlorine-based sanitizers is widespread throughout the fresh produce industry in the process water to maintain microbial safety of produce, avoid cross-contamination and recycle water. In this study, alternative disinfection technologies were investigated due to the negative reports showing chlorine instability in the presence of organic matter and the undesirable by-product residues. Tsunami ® (15.2% peroxyacetic acid and 11.2% hydrogen peroxide) and high-power ultrasound (HPU, 0.56 kW/l, 20 kHz), alone or in combination, were evaluated in lettuce process water analyzing their ability to reduce MNV during either produce washing or water recycling. PAA concentrations of 6.4, 12.8 and 16 mg/l as well as HPU were insufficient for application in the produce washing tank where a rapid MNV inactivation is required. In contrast, a complete rapid inactivation of MNV (7.4 log TCID50 ) was recorded when 80 mg/l of PAA was used. For recycled water reconditioning, HPU was applied and no virus reduction was observed. Two PAA concentrations (6.4 and 12.8 mg/l) that can be found in the recycled water were also tested. The MNV inactivation was faster at 12.8 mg/l than at 6.4 mg/l of PAA with 2.6 and 2 log reductions after 20 min contact. One additional log reduction was achieved 20 and 40 min later, respectively. MNV inactivation fitted the Bipashic model well. A contact time of 95 and 115 min would be required to obtain the complete elimination of MNV (4.4 log TCID50 ) by 6.4 and 12.8 mg/l of PAA. PAA efficacy was not enhanced by the combination with HPU in contrast to the inactivation of pathogenic bacteria tested in other studies. This indicates that viruses are more resistant to this hurdle technology than pathogenic bacteria such as Escherichia coli O157:H7, Salmonella and other HPU conditions such as higher frequencies and combination of HPU with other physical treatments need to be explored. Highlights: Murine norovirus inactivation in fresh-cut process water (COD 500 mg/l) was tested. Complete inactivation of MNV (7.4 log TCID50 ) was reported by 80 mg/l of PAA. Lower efficacy for MNV inactivation by residual concentrations of PAA. Efficacy of PAA was not improved when combined with high power ultrasound. PAA can be a good alternative to chlorine for produce washing and water recycling.